2018
DOI: 10.1101/419200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insulin Producing Cells Monitor the Cold and Compensate the Cold-Induced Sleep in Drosophila

Abstract: Sleep is regulated by environmental factors including temperature, but the neural circuits that receive the sensory signal and mediate the regulation remain unclear. We examined how cold could influence Drosophila sleep patterns and its neural mechanism. The results showed that Drosophila has more sleep duration, less sleep latency and deeper sleep depth under cold condition. We identified the Insulin-producing Cells (IPCs) can be activated by cold, and receive the cold signal from the 11216 cold-sensing neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Since a lower level of feeding results in the suppression of energy expenditure, the dormancy-inducing low temperature might negatively affect IPC activity, possibly leading to reproductive dormancy. Meanwhile, curiously and paradoxically, some studies have reported that IPCs are activated by cold-sensing neurons at 18 • C rather than 25 • C (Li and Gong, 2015;Zhang et al, 2019), whereas the function of cold-sensing neurons in dormancy-inducing conditions has not yet been investigated. Further studies will be needed to clarify how low temperatures influence IPC activity to induce reproductive dormancy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Since a lower level of feeding results in the suppression of energy expenditure, the dormancy-inducing low temperature might negatively affect IPC activity, possibly leading to reproductive dormancy. Meanwhile, curiously and paradoxically, some studies have reported that IPCs are activated by cold-sensing neurons at 18 • C rather than 25 • C (Li and Gong, 2015;Zhang et al, 2019), whereas the function of cold-sensing neurons in dormancy-inducing conditions has not yet been investigated. Further studies will be needed to clarify how low temperatures influence IPC activity to induce reproductive dormancy.…”
Section: Future Perspectivesmentioning
confidence: 99%